Igalan induces detoxifying enzymes mediated by the Nrf2 pathway in HepG2 cells - Lee, Kyung-Mi; Shin, Ji Min; Chun, Jaemoo; Song, Kwangho; Nho, Chu Won; Kim, Yeong Shik (WILEY, 2019)
Igalan is one of the sesquiterpene lactones found in Inula helenium L., which is used as the traditional medicine to treat inflammatory diseases. However, the pharmacological effects of igalan have not been characterized. In this study, we isolated igalan from I. helenium L. and evaluated the effects of igalan on signaling pathways and expression of target genes in HepG2 cells. Igalan activated the nuclear factor erythroid 2-related factor 2 (Nrf2) pathway by increasing the inactive form of GSK3 beta, the phosphorylated form of AKT, and the nuclear accumulation of Nrf2. Thus, target genes of Nrf2 such as HO-1 and NQO1 increased in HepG2 cells. Moreover, igalan inhibited the tumor necrosis factor-alpha (TNF-alpha)-induced nuclear factor-kappa B activation and suppressed the expression of its target genes, including TNF-alpha, interleukin (IL)-6, and IL-8 in HepG2 cells. Our results indicate the potential of igalan as an activator of cellular defense mechanisms and a detoxifying agent.
Keywords: NF-KAPPA-B; ANTIOXIDANT RESPONSE ELEMENT; GLYCOGEN-SYNTHASE KINASE-3-BETA; NRF2-MEDIATED INDUCTION; GENE-EXPRESSION; NUCLEAR EXPORT; ACTIVATION; STRESS; KINASE; PHOSPHORYLATION